PENERAPAN SENI BODY PAINTING UNTUK MENINGKATKAN PRESTASI BELAJAR RIAS FANTASI PADA MAHASISWA AKS-AKK YOGYAKARTA - Harwiyati, Enny (Jurnal Socia Akademika, 2023)
The purpose of the research is to improve the learning achievement of the Cosmetology study program students in the Fantasy Makeup course at AKS-AKK Yogyakarta. The method used in this study uses a quantitative approach. Determination of research subjects using sampling techniques. The number of panellists in this study was 48 students in the V semester of Cosmetology in 2020 and the class of 2021. Data collection techniques use observation, test assignments, and documentation. Statistical data analysis techniques. The results of research on the assessment aspect, namely the value of power. Theme creativity by 83%, body painting value by 85%, makeup and face painting value by 86%, hair styling value by 77%, costume and accessories value by 83%, and total look value by 85%. So 5 aspects of value are included in the high-category assessment, and aspects of hair styling scores are included in the medium-category assessment